The determination of mercury levels in the blood and hair of rabbits with amalgam fillings - Yerebasan, Ülkü; Servi, Kadir; Ataş, Osman; Doğan, Mehmet Sinan (My University, 2020)
Aim: This study was conducted to investigate the level of mercurytransmitted into the blood and hair of rabbits based on the number ofamalgam-filled teeth present in the mouth.Methodology: A total of 18 male rabbits from New Zealand were usedin the study. The rabbits were separated into 3 groups: a control group,a dichotomous amalgam-filled group, and a quadruple amalgam-filledgroup. Blood samples were collected from the animals before fillings andafter 24 hours, one week and one month after the fillings were applied.Hair samples were taken before the fillings were applied and at onemonth after. Blood and hair samples were taken from the rabbits, andthe transfer of mercury was measured with the hydride system in theabsorption spectrophometer.Results: The data obtained from the study were evaluated using theSPSS 21 package program. As compared with the control group at the 24thhour, no statistical difference was seen between the dichotomous andquadruple amalgam filling groups in terms of blood mercury level(P>0.05). However, the levels of blood mercury observed one week andone month later were significantly higher than in the control groupobserved at the same times (p<0.05). Over each time period measured,the level of blood mercury was found to be similar between dichotomousand quadruple amalgam filling groups (p>0.05).Conclusion: Mercury could not be detected in hair samples. As a result,it was revealed that amalgam fillings affect the blood mercury level.
Keywords: Diş Hekimliği; Kimya; Tıbbi